2008
DOI: 10.1017/s0007114507886326
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and metabolic effects of cis-9, trans-11-conjugated linoleic acid in subjects with birch pollen allergy

Abstract: Animal studies suggest that conjugated linoleic acid (CLA) may modulate the immune response, while studies in healthy human subjects have shown little effect and results are controversial. However, the effects of CLA may be more prominent in situations of immune imbalance, such as allergy. We studied the effects of the natural CLA isomer, cis-9, trans-11-CLA, on allergy symptoms and immunological parameters in subjects with birch pollen allergy. In a randomised, placebo-controlled study, forty subjects (20-46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 49 publications
(73 reference statements)
6
43
0
1
Order By: Relevance
“…13 In another clinical trial, CLA (cis-9,trans-11 isomer) supplementation in those with birch pollen allergy decreased the in vitro production of TNF-α. 34 The finding of the present study is in agreement with results of the above-mentioned studies. 13,[32][33][34] Another result of this study was that IL-1β decreased slightly in the CLA group while increasing in the placebo group.…”
Section: Discussionsupporting
confidence: 94%
“…13 In another clinical trial, CLA (cis-9,trans-11 isomer) supplementation in those with birch pollen allergy decreased the in vitro production of TNF-α. 34 The finding of the present study is in agreement with results of the above-mentioned studies. 13,[32][33][34] Another result of this study was that IL-1β decreased slightly in the CLA group while increasing in the placebo group.…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies carried out in young animals have shown that immune function is enhanced after feeding c 9,t11 CLA isomer (18,19). The immune effects of CLA have been also seen in healthy and ill individuals (20,21). However, little work has been done on the effects of CLA during the early postnatal periods (lactation or infancy), and even less during the prenatal period (gestation).…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is the first study demonstrating the in vitro anti-allergic effect of CLNAs on HMC-1 cells, and this is in line with earlier findings showing that CFAs, such as CLAs, may possess anti-allergic activities. For example, Jaudszus et al (24) reported that 9Z, 11E-CLA could inhibit allergic sensitization and airway inflammation through peroxisome proliferator-activated receptor-γ dependent mechanism in mice, whereas others demonstrated that human healthy volunteers supplemented with 9Z, 11E-CLA resulted in a decreased plasma IgE level and reduced secretion of IL-5 by PBMCs (25,26). Despite these earlier findings, the underlying action mechanisms for the anti-allergic effects of CFAs, such as CLAs and CLNAs, remain poorly understood and further studies are required to elucidate the mechanisms, in vitro and in vivo, for the anti-allergic activity of CFAs.…”
Section: A B C Dmentioning
confidence: 99%